Application of the T Agility Test to assess functional stability in II-league footballers - Kuchciński, Kacper; Szczypiór-Piasecka, Karina; Mińko, Alicja; Antczak, Krzysztof; Orłowska, Aleksandra (Journal of Education, Health and Sport, 2021)
INTRODUCTION: T agility Test is a test designed to assess functional stability as well as multidirectional movement. This test can be used to test players of various sports in relation to the speed of their movements, including football, handball or basketball. Football as a contact sport is characterized by many injuries acquired during training or during a match. Lower limb joints such as the hip joint, knee joint and ankle joint are the most vulnerable. OBJECTIVE: 1. Comparison of functional stability in football players of the II league team. 2. Impact of injury on T agility Test result. 3. Usefulness of the Test agility to assess the functional stability of athletes in the training process.MATERIAL AND METHODS: 24 players from the professional football team Blue Stargard were tested. The study was conducted at the beginning of the autumn round of the 2019/2020 season. The competitors were from 21 to 42 years old, the average weight was 77 kg, the average height was 184 cm and average BMI was 22.7. A questionnaire was used to subjectively assess the players' health, while the T agility Test was used to assess the functional status of the players. RESULTS: The best T agility test result obtained in the research group was 9.1s. Positive reports were obtained during the Pearson Correlation T agility Test with age, weight, height and training experience. Significance test in everyone of the cases showed there were no significant differences (p> 0.999). CONCLUSIONS: 1. Foot footballers have good functional stability. 2. Past injuries do not affect the achieved T agility Test result. 3.T agility Test is useful for assessing dynamic stability in athletes.